Asuhan Keperawatan Pada Ny. U Keluarga Tn. Sl Dengan : Diabetes Melitus Di Desa Kutayu RT 05 RW 02 Kecamatan Tonjong Kabupaten Brebes - Meli Afrilia; Ahmad Zakiudin; Esti NurJanah (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Diabetes mellitus is a serious problem in public health and one of the four priority non-communicable diseases that are of global concern (Dewi, 2022). The etiology of type 2 diabetes mellitus is insulin resistance, with higher than normal insulin concentrations required to maintain normoglycemia. When insulin production by pancreatic beta cells is inadequate to compensate for increased insulin resistance, blood glucose levels will increase. Secondly, pancreatic beta cell dysfunction occurs as a result of a combination of genetic and environmental factors. Lastly, environmental factors which also play an important role in the occurrence of DM are obesity, eating too much and lack of physical activity (Dewi, 2022). Diabetes mellitus was the direct cause of death for 1.6 million people in 2016. The latest data released by the International Diabetes Federation (FDA) shows that around 415 million people aged 20-79 years worldwide experienced diabetes mellitus in 2015. This figure is predicted will increase to 642 million people in 2040 with prevalence increasing from 8.8% to 10.4%. China, India and the United States are the three countries with the highest number of diabetes mellitus sufferers. According to the World Diabetes Foundation, from 2014 until now 382 million people in Indonesia suffer from diabetes mellitus. This number is predicted to increase to 592 million people in 2035 (Maria, 2021).